IMPLEMENTASI STRATEGI PEMBIASAAN TERINTEGRASI DALAM PENGUATAN KARAKTER RELIGIUS DAN SOCIAL AWARENESS PESERTA DIDIK DI SDN 01 SIDOHARJO JATI AGUNG LAMPUNG SELATAN - Ummi rohmiyati; An An Andari; Cipto Handoko (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to analyse in depth how the implementation of an integrated habituation strategy can strengthen students' religious character and social awareness at SDN 01 Sidoharjo Jati Agung, South Lampung, as a systematic effort to respond to the challenge of character value degradation at the primary education level. The research employs a qualitative approach with a case study design to understand the implementation of the integrated habituation strategy in reinforcing students' religious character and social awareness at SDN 01 Sidoharjo Jati Agung, South Lampung. The research subjects include the principal, teachers, and students directly involved. Data were collected through participatory observation, in-depth interviews, and documentation of school programs. The analysis was carried out thematically through data reduction, data display, and conclusion drawing. Data credibility was maintained through triangulation and member checking. This method produced an in-depth picture of the effectiveness of the integrated habituation strategy in shaping students' character. The findings show that the implementation of the integrated habituation strategy at SDN 01 Sidoharjo Jati Agung is carried out consistently and has become part of the school culture, supporting the strengthening of students' religious character and social awareness. Structured and repetitive religious habituation contributes to the internalisation of values such as faith, discipline, honesty, and responsibility, which are reflected in students' daily behaviour. In addition, social activities such as group work, joint cleaning, and peer interaction enhance students' empathy, concern for others, and social compliance. This strategy forms whole, ethical, and socially sensitive character, affirming that integrated habituation is an effective mechanism for comprehensive character education in elementary schools.